Design of a circular patch antenna for 3D printing - Mohd Ramly, Athirah; Abdul Malek, Norun; Mohamad, Sarah Yasmin; Ahamad Sukor, Masturah (IEEE, 2016)
This paper proposed an innovative circular patch antenna using the 3D printing technique that resonated at 2.33GHz. The purpose of using 3D printing is a way to reduce cost and time in fabrication of the antenna. By introducing a new material to the subject which is Acrylonitrile Butadiene Styrene (ABS) as the substrate of the antenna, the cost can be greatly reduced. Furthermore, a coaxial probe feed is used and it is said to be easy to fabricate, matched and has low spurious radiation. The feeding method that has been used in this research is a coaxial line feeds where the inner conductor of the coax is connected to the patch meanwhile the conductor is connected to the ground. This antenna is designed on an ABS substrate with εr = 3.5. The thickness is said to be 3.25mm. In addition to that, it has the return loss (S11) of -24.487 dB at 2.335GHz. The whole designation of the antenna is by using Computer Simulation Technology (CST) software. The anticipated design of a circular patch antenna can be extended to 3D antenna arrays and therefore, the prototype will become more compact, efficient and robust.